Adsorption of Textile Dyes Using (L.) Fibres: Equilibrium and Kinetics Modelling - Aïcha Menyar Ben Hamissa; François Brouers; Borhane Mahjoub; Mongi Seffen (Adsorption Science & Technology)
This study was carried out to examine the potential of Agave americana fibres (AAF) for the treatment of wastewater contaminated with dyes. The batch mode adsorption of two dyes, viz. Sumfixe Supra Red (SSR) and Alpacelle Lumiere Brown (ALB), by AAF was investigated at different pH values, temperatures and initial dye concentrations. The highest dye adsorption capacities at 30°C were attained at pH 2.0 for SSR and at pH 2.5 for ALB. In both cases, an increase in temperature increased the velocity of the reaction. The maximum amounts of dyes desorbed were at basic pH values. To compare our results with studies on other biomaterials, the adsorption isotherms and kinetic data were analysed employing the usual models (Freundlich, Langmuir and Temkin isotherms and first- and second-order kinetics). Conventional analysis indicated that the kinetics of the processes were closer to pseudo-second order rather than first order. The data were also modelled with a new method of analysis based on the statistical theory of complex systems and the heterogeneity of the sorption energy (energy landscape). This enabled the adsorption process to be characterised in terms of a greater number of physical parameters.